(untitled) (Conferencea, 2024)
This article explores the methodological issues in Uzbek prose, focusing on its historical development and theoretical foundations. It delves into various approaches that shaped Uzbek prose, from realism in the Jadid period to socialist realism in the Soviet era, and the diversity of modern techniques in the post-independence period. Specific examples such as Abdulla Qodiriy’s "O’tgan kunlar," Oybek’s "Navoiy," and Tohir Malik’s "Shaytanat" are analyzed to highlight the application of different methodologies. Contemporary trends, including structuralism, psychoanalysis, postcolonialism, and gender studies, are also discussed as tools for examining Uzbek prose’s artistic and social significance.